Epistemologi Kalam - Misrah (Wahdatul Ulum Institute, 2022)
The solution to kalam will always expand according to demand reality of epoch. When demand (threat) come, kalam come and meresponnya. A period of classical have come to the history strengthen the demand kalam from ideology attack. Now kalam just needed to attend to answer problematika is more idea in modernity